PELATIHAN HIDROPONIK, AKSI HIJAU WARGA: MERAKIT HIDROPONIK GUNA MEWUJUDKAN KETAHANAN PANGAN LOKAL - Suyanto, Agus; Nurfitria, Rima; Widarti, Sri; Andayani, Sri; Setiawan, Setiawan; Suryani, Rini; Astar, Ismail; Dominikus Bancin, Hardi; Tutik Purwani Irianti, Agnes; Rahayu, Sri; Ellyta, Ellyta; Asti, Asti; Yuliana Ayen, Rosalina; Oktarianti, Sherly; Aini, Fitriana (LPPM Universitas Panca Bhakti, 2025)
Hydroponic cultivation training was conducted for residents of Hydroponic cultivation training was conducted for 40 residents of Gang Kuini I Jeruju, West Pontianak District, aiming to address limited land availability and support local food security. This community service program utilized a participatory approach through socialization, hands-on training, and mentoring. The main issues addressed included narrow land constraints, lack of knowledge about modern agricultural technology, and community dependence on vegetable markets for daily needs. The training introduced wick system hydroponics using simple materials that were easy to implement in household yards. The methods included needs assessment, training preparation, technical socialization, hands-on hydroponic equipment construction, seedling planting, and post-training evaluation. Pre-test and post-test evaluation results showed significant improvements: knowledge aspect increased from 41% to 86%, and attitude aspect increased from 50% to 89%. Results showed that 88% of participants expressed interest in trying hydroponics, and 90% believed hydroponics supports local food security. This activity contributed positively toward household food security by enabling residents to produce fresh vegetables sustainably. The training fostered a green movement among residents while reducing household food expenditures and enhancing nutritional quality for families.